(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Yellow oleander (Thevetia peruviana) is a commonly found shrub in India which produces multiple alkaloids which are cardiotoxic. Numerous cases of yellow oleander poisoning have been reported in humans. The spectrum of toxicity due to this plant ranges from nausea, vomiting, diarrhoea, electrolyte abnormalities and arrhythmias in humans. No case of bowel necrosis due to yellow oleander has been reported in humans to the best of our knowledge. We present a case of 45-year-old female with suicidal consumption of crushed yellow oleander seeds. The patient was admitted and observed for arrhythmias. On day 2 of admission, she developed bloody stools, hematemesis and abdominal pain. Abdominal examination showed rigidity and per rectal examination showed blood-stained mucoid stools. A CECT was done which showed findings suggestive of gastric necrosis with perforation. The patient was taken up for surgery and stomach was found to be gangrenous with a perforation at the greater curvature. Total gastrectomy was performed. The post operative biopsy showed extensive transmural coagulative necrosis of the stomach and lymphoplasmacytic infiltration of the submucosa. Necrosis of bowel has been reported in experimental settings in animals and in cattle poisoning but no reported case of stomach necrosis and perforation due to yellow oleander has been reported in humans. As yellow oleander is a commonly used suicidal poison in Southern Asia, an eye needs to be kept out for gastrointestinal symptoms. We conclude with recommendations on management of yellow oleander poisoning in the light of these new manifestations.